Asphalt and Asphalt Mixtures - Zhang, Haitao (IntechOpen, 2019)
In recent years, with the rapid development of the world transportation industry, the proportion of asphalt pavement in road engineering is increasing. Therefore, while the demand for asphalt and asphalt mixture is increasing, the quality requirements for materials are also improving. In particular, new materials and new technologies are constantly emerging, and the application technology, theory, and technical specifications of asphalt materials have made great progress.